TO THE SOURCES OF DIACHRONIC SOCIOLINGUISTICS: GLOBAL EXPERIENCE AND UKRAINIAN PROBLEMATICS - І. Д. Фаріон (Записки з українського мовознавства, 2017)
The subject of the suggested research is a new sphere of sociolinguistics – diachronic sociolinguistics: its sources, subject of the research and tasks. A famous researcher Orest Tkachanko was first among Ukrainian linguists who paid attention to problems of the methodology of diachronic linguistics. Polish researches, in particular Witold Taszycki and Barbara Otwinowska, suggested a unique sociohistorical factual collation and analysis of sociolinguistic factors against the background of philosophic and cultural dimensions of a changeable epoch. The centennial path of the scientific understanding of the new subject of the research led to the gradual divergence of three historical disciplines with its definitions and research procedures: historical grammar (history of internal structure of the language), history of literary language (history of the functional style of the literary language) and diachronic sociolinguistics (history of social pressure on the language and language on society). In the late 20th century, diachronic sociology defined its key research problems from the development of language social functions, determined because of the language status, to the problems of language reception, language reflections and lingual consciousness that resulted in the reclassification of languages and dialects interaction and creation of socially important koine. Problems of the historic codification of language norms can be considered as a triumph  of the diachronic sociolinguistics. There is still development and stabilization of definitions and unique research methods.